2023
DOI: 10.3390/su15076254
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment Applied to End-of-Life Scenarios of Sargassum spp. for Application in Civil Construction

Abstract: Environmental risks and vulnerabilities in coastal regions include the massive deposits of brown algae of the genus Sargassum in regions such as the Caribbean, Gulf of Mexico, and northern Brazil. Efforts have been made to turn this problem into an opportunity by seeking new uses for this biomass in the sectors of food, agriculture, health, biofuels, bioremediation, and civil construction. Thus, this study aimed to produce quantitative data for different end-of-life scenarios of the Sargassum algae, seeking fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The sargassum biomass (Figure 2) used to produce ash was collected in the municipality of Carutapera-MA (Brazil), specifically in the region of São Pedro beach. According to Bueno et al, (2023) [25], the composition of the brown algae found in this region is as follows: Sargassum fluitans III (50%), Sargassum natans I (15%), and Sargassum natans VIII (35%). The sargassum ash was obtained by means of a 10013 Jung resistive oven with 7000 W, a burning temperature of 500 • C for two hours, and a heating rate of 10 • C/min.…”
Section: Characterization Of Raw Materialsmentioning
confidence: 87%
See 2 more Smart Citations
“…The sargassum biomass (Figure 2) used to produce ash was collected in the municipality of Carutapera-MA (Brazil), specifically in the region of São Pedro beach. According to Bueno et al, (2023) [25], the composition of the brown algae found in this region is as follows: Sargassum fluitans III (50%), Sargassum natans I (15%), and Sargassum natans VIII (35%). The sargassum ash was obtained by means of a 10013 Jung resistive oven with 7000 W, a burning temperature of 500 • C for two hours, and a heating rate of 10 • C/min.…”
Section: Characterization Of Raw Materialsmentioning
confidence: 87%
“…Secondary data were used for the LCI. Information on sargassum ash, as well as its decomposition on beaches and landfills, was collected from the study by Bueno et al, (2023) [25]. Data relating to other processes were obtained from Ecoinvent 3.7.1.…”
Section: Life Cycle Inventory (Lci)mentioning
confidence: 99%
See 1 more Smart Citation
“…The LCA was carried out with the GaBi 6 software, using secondary databases, with Eucalyptus production and the MDP panel production inputs and output taken from the "SICV Brasil" LCA database [sicv.acv.ibict.br]. The processing for sargassum was taken from Bueno et al [42] and the other Ecoinvent 3.7.1 processes. Table 2 presents the secondary data used for multilayer particleboards's LCA.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…The LCA was carried out with GaBi 6 software, using secondary databases, with Eucalyptus production and the MDP panel production inputs and output taken from the "SICV Brasil" LCA database [https://sicv.acv.ibict.br/] (accessed on 6 February 2024). The processing for sargassum was taken from Bueno et al [45] and the other Ecoinvent 3.7.1 processes. Allocation was avoided for all production stages, except for the sugarcane bagasse, where the current Ecoinvent 3.7.1 process already presents its mass allocation impacts.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%